Myxospora guizhouensis (Hypocreales, Stachybotryaceae), a new soil-borne species from Guizhou, China - Wang, Yunli; Zhu, Liping; Chen, Hui; He, Yingzi; Li, Qirui; Wang, Yao (Phytotaxa, 2026)
The family Stachybotryaceae (Hypocreales) has recently undergone substantial taxonomic revision, with multilocus phylogenetics revealing numerous cryptic lineages. During a survey of soil fungi in Guizhou Province, China, a myrothecium-like fungus was isolated and is here described as Myxospora guizhouensis sp. nov. based on morphological and molecular evidence. The new species is characterized by solitary, hyaline, flask-shaped to cylindrical conidiogenous cells arising directly from vegetative hyphae, and by solitary, acrogenous conidia that are globose to limoniform, hyaline, aseptate, thin-walled, and smooth. Phylogenetic analyses of a combined ITS, nrLSU, tef-1α, rpb2, tub2, and cmdA dataset using maximum likelihood and Bayesian inference resolve M. guizhouensis as a distinct, well-supported lineage within Myxospora, closely related to M. crassiseta. Both morphological comparisons and molecular phylogenetic data support the recognition of M. guizhouensis as a new species, representing the first Myxospora species reported from soil in China.